The chemopreventive effects of Saussurea salicifolia through induction of apoptosis and phase II detoxification enzyme - Kang, Kyungsu; Lee, Hee Ju; Kim, Chul Young; Lee, Saet Byoul; Tunsag, Jigjidsuren; Batsuren, Dulamjav; Nho, Chu Won (PHARMACEUTICAL SOC JAPAN, 2007)
The ethanol extract of the aerial part of the Mongolian medicinal plant Saussurea salicifolia induced a dose-dependent cell growth inhibition in both human gastric adenocarcinoma AGS cells and mouse hepatoma Hepa 1c1c7 cells (IC50=30.22 and 116.96 mu g/ml), respectively. The extract induced an apoptosis in AGS cells inference from the externalization of the phosphatidylserine, the increase of the sub G0/G1 content (%) and the apoptotic morphological changes including membrane blebbing, the formation of apoptotic bodies and chromatin condensation. In order to identify active substances causing the apoptosis, we further isolated major compounds present in Saussurea salicifolia and 7 compounds were isolated including a sesquiterpene lactone, cynaropicrin, 3 lignans (trachelogenin, matairesinol and arctigenin) and 3 lignan glycosides (tracheloside, matairesinoside and arctiin). In general the lignan aglycones were more cytotoxic than their lignan glycosides in both AGS cells and Hepa 1c1c7 cells. Cynaropicrin not only showed the most potent cytotoxicity among the 7 major compounds but also it induced an apoptosis and a weak G2/M arrest in AGS cells. Arctigenin had the second-best cytotoxicity among 7 major compounds, and induced an apoptosis. In order to evaluate the induction of the phase 11 detoxification enzyme, we measured the induction of quinone reductase activity of the extract, fractions and compounds in Hepa 1c1c7 cells. The ethyl acetate fraction and aretigenin showed the strongest cancer chemopreventive activity (chemoprevention index=9.88 and 7.57, respectively). These data suggest that the extract as well as the lignan compounds (especially arctigenin) originated from Saussurea salicifolia may be served as potential cancer chemopreventive agents for prevention or treatment of human cancers.
Keywords: QUINONE REDUCTASE; SESQUITERPENE LACTONES; MAMMALIAN LIGNANS; CANCER; PHYTOESTROGENS; PRECURSORS; AGENTS; CELLS; LAPPA